An evaluation tool for myofascial adhesions in patients after breast cancer (MAP-BC evaluation tool): Development and interrater reliability - De Groef, An; Van Kampen, Marijke; Vervloesem, Nele; De Geyter, Sophie; Dieltjens, Evi; Christiaens, Marie-Rose; Neven, Patrick; Geraerts, Inge; Devoogdt, Nele (PLOS ONE, 2017)
Purpose To develop a tool to evaluate myofascial adhesions objectively in patients with breast cancer and to investigate its interrater reliability. Methods 1) Development of the evaluation tool. Literature was searched, experts in the field of myofascial therapy were consulted and pilot testing was performed. 2) Thirty patients (63% had a mastectomy, 37% breast-conserving surgery and 97% radiotherapy) with myofascial adhesions were evaluated using the developed tool by 2 independent raters. The Weighted Kappa (WK) and the intra-class correlation coefficient (ICC) were calculated. Results 1) The evaluation tool for Myofascial Adhesions in Patients with Breast Cancer (MAP-BC evaluation tool) consisted of the assessment of myofascial adhesions at 7 locations: axillary and breast region scars, musculi pectorales region, axilla, frontal chest wall, lateral chest wall and the inframammary fold. At each location the degree of the myofascial adhesion was scored at three levels (skin, superficial and deep) on a 4-points scale (between no adhesions and very stiff adhesions). Additionally, a total score (0–9) was calculated, i.e. the sum of the different levels of each location. 2) Interrater agreement of the different levels separately was moderate for the axillary and mastectomy scar (WK 0.62–0.73) and good for the scar on the breast (WK >0.75). Moderate agreement was reached for almost all levels of the non-scar locations. Interrater reliability of the total scores was the highest for the scars (ICC 0.82–0.99). At non-scar locations good interrater reliability was reached, except for the inframammary fold (ICC = 0.71). Conclusions The total scores of all locations of the MAP-BC evaluation tool had good to excellent interrater reliability, except for the inframammary fold which only reached moderate reliability.